1980
DOI: 10.1111/j.1365-2621.1980.tb06519.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Magnesium Bioavailability From Acid‐precipitated and Neutralized Soybean Protein Products

Abstract: The bioavailability of zinc (Zn) and magnesium (Mg) from soy protein products freeze‐dried at different pH's was investigated. Soy concentrates and isolates were produced by both acid precipitation (acid soy) or acid precipitation with subsequent neutralization to pH 7.0 (neutral soy). The bioavailability studies involved feeding growing rats isonitrogenous and isocaloric diets based on egg white (with added ZnCO3 or MgCO3) or soy product (substituted in egg white diets to provide equivalent Zn or Mg). Linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Phytic acid ϫ Ca:Zn molar ratio is considered to be a reliable predictor of zinc bioavailability in processed products (Fordyce et al, 1987;Lonnerdal et al, 1988;Likuski and Forbes, 1965;Zhou et al, 1992). Also, the type of processing of soy products affects zinc bioavailability (Erdman et al, 1980;Erdman and Forbes, 1981;Erdman and Fordyce, 1989). In our experiments, dietary calcium and zinc concentrations were nearly the same for both soy treatment groups, so processing and zinc bioavailability differences would be the only potential factors differentiating the two groups.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Phytic acid ϫ Ca:Zn molar ratio is considered to be a reliable predictor of zinc bioavailability in processed products (Fordyce et al, 1987;Lonnerdal et al, 1988;Likuski and Forbes, 1965;Zhou et al, 1992). Also, the type of processing of soy products affects zinc bioavailability (Erdman et al, 1980;Erdman and Forbes, 1981;Erdman and Fordyce, 1989). In our experiments, dietary calcium and zinc concentrations were nearly the same for both soy treatment groups, so processing and zinc bioavailability differences would be the only potential factors differentiating the two groups.…”
Section: Discussionmentioning
confidence: 58%
“…Also, the type of processing of soy products affects zinc bioavailability (Erdman et al, 1980;Erdman and Forbes, 1981;Erdman and Fordyce, 1989). In our experiments, dietary calcium and zinc concentrations were nearly the same for both soy treatment groups, so processing and zinc bioavailability differences would be the only potential factors differentiating the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…The bioavailability of zinc from soy protein products has been found to be highly variable (Erdman et al 1980). Reported differences in zinc utilization from soy isolates of the same phytate content 274 C. A. PRATTLEY, ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the preparation of soya protein isolates and concentrates with reduced phytate contents to avoid Zn deficiencies in human infants has been a goal for decades (53) . As discussed by Erdman (54) , protein concentrates with reduced phytate contents can be prepared by exploiting the capacity of phytate to bind protein, which has been demonstrated in soya (55) and rapeseed (56) , and the fate of phytate following the preparation of soya protein concentrates/isolates has been reviewed (57) . In relation to ternary complexes and protein availability, Champagne et al (58) suggested that the protein moiety of ternary complexes is comprised of either amino acids or small peptides and it then follows that the amount of protein bound in ternary complexes in the small intestine may not be sufficient to compromise amino acid digestibility (9) .…”
Section: Ternary Protein -Phytate Complexesmentioning
confidence: 99%